Penyelenggaraan Program Taman Bacaan Masyarakat Berbasis Kualitas Hidup Sebagai Relawan Magang Ruang Belajar Aqil (Studi Deskriptif Di Taman Bacaan Masyarakat Pondok BK Pakis Malang) - Mita Romanika Fitria; Budi Prabowo (Universitas 45 Surabaya, 2023)
This article aims to identify and map the potential of community reading gardens (TBM) and target areas through programs and services, design and prepare empowerment activities according to community needs and profiles, manage and implement community empowerment programs and services, map the impact of programs and community empowerment services, and coordinate and cooperate with the team. TBM is a non-formal education unit, which was established and managed by the community itself with the aim of increasing their knowledge and skills, as well as their talents so that they can improve their quality of life, including increasing their income. It is not uncommon for TBMs to face problems and obstacles in improving their functions and performance, especially in implementing quality-of-life-based programs for the community. In this article, the study used is the reading garden of the Pondok BK Sekar Wijaya community, Pakis, Malang, with the subject of children to the people of Pucangsongo village, Pakis, Malang. Using a qualitative approach, with literature that refers to theoretical/theoretical studies and other references with the aim of finding out some knowledge information which later the information obtained will be implemented to the practice of implementing community programs and services